2019
DOI: 10.1093/annonc/mdz012
|View full text |Cite
|
Sign up to set email alerts
|

OlympiAD final overall survival and tolerability results: Olaparib versus chemotherapy treatment of physician’s choice in patients with a germline BRCA mutation and HER2-negative metastatic breast cancer

Abstract: Background In the OlympiAD study, olaparib was shown to improve progression-free survival compared with chemotherapy treatment of physician’s choice (TPC) in patients with a germline BRCA1 and/or BRCA2 mutation (BRCAm) and human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (mBC). We now report the planned final overall survival (OS) results, and describe the most common adverse events (AEs) to better understand ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
433
0
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(536 citation statements)
references
References 7 publications
11
433
0
26
Order By: Relevance
“…The median OS with olaparib compared with treatment of physician's choice was 19.3 months versus 17.1 months, respectively (HR, 0.90; 95% CI, 0.66-1.23; P5.513). 113 QOL was significantly better in the olaparib arm. It is interesting to note that patients who had not received prior chemotherapy in the metastatic setting achieved a 7.9-month longer median OS compared with treatment of physician's choice.…”
Section: Systemic Therapy For Recurrent or Stage IV Disease With Germmentioning
confidence: 87%
See 1 more Smart Citation
“…The median OS with olaparib compared with treatment of physician's choice was 19.3 months versus 17.1 months, respectively (HR, 0.90; 95% CI, 0.66-1.23; P5.513). 113 QOL was significantly better in the olaparib arm. It is interesting to note that patients who had not received prior chemotherapy in the metastatic setting achieved a 7.9-month longer median OS compared with treatment of physician's choice.…”
Section: Systemic Therapy For Recurrent or Stage IV Disease With Germmentioning
confidence: 87%
“…It is interesting to note that patients who had not received prior chemotherapy in the metastatic setting achieved a 7.9-month longer median OS compared with treatment of physician's choice. 113 In the phase III EMBRACA trial, patients with advanced breast cancer harboring the germline BRCA mutations to a PARP inhibitor were randomized to talazoparib (n5287) or to physicians choice of single-agent chemotherapy (n5144). 114 The median PFS among patients in the talazoparib group was longer than the control group (8.6 months [95% CI, 7.2-9.3] vs 5.6 months [95% CI, 4.2-6.7]; HR for disease progression or death, 0.54; 95% CI, 0.41 to 0.71; P,.001).…”
Section: Systemic Therapy For Recurrent or Stage IV Disease With Germmentioning
confidence: 99%
“…During the last years, new drugs such as the Poly(ADP-ribose) polymerase (PARP)-inhibitors targeting HRR-defective tumors were studied in several clinical trials. Two different phase III trials (OlympiaAD and EMBRACA) showed an improved response rate and PFS for PARP inhibitor (Olaparib or Talazoparib)-treated patients compared to patients who received standard chemotherapy [10,11]. Among the new therapeutics Eribulin, a non-taxane microtubule inhibitor, demonstrated an improved overall survival (OS) in patients with MBC already treated with taxane and anthracycline compared to treatment with physicians' choice in the EMBRACE trial [12].…”
mentioning
confidence: 99%
“…Beyond chemotherapy, the use of first-line single-agent PARP-inhibitors might be an option, based on the intriguing ORR and PFS results observed in phase 3 OLYMPIAD and EMBRACA trials [15][16][17]. Furthermore, hormonal therapy might be still appropriate in hormone-receptor-positive BRCA1/2 mutated BC diseases without visceral crisis.…”
Section: Brca1/2 Mutations and Platinum Saltsmentioning
confidence: 99%